ANALISIS INDEKS KINERJA SISTEM IRIGASI DI DAERAH IRIGASI PAPAH, KULON PROGO - , YAZID SALAM, Ir. Sukirno., MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the major problems that occur in the supply of irrigation water is the decreasing of the water availability at certain time. Irrigation system in Kulon Progo has different character, because there are is a connectivity among irrigation area which is located in headwaters and downstream trough natural chanel. It is formed by drainage as well as river. This study specifically discuss about the performance of Papah irrigation system, Kulon Progo, D.I Yogyakarta based on the Regulation of the Minister of Public Works Blank Attachment No. 32/PRT/M/2007 about the irrigation System performance index of the infrastructure physical condition, the plant productivity, supporting facilities, personel organitation, documentation, and P3A. From the results of calcuations obtained that the irrigation System Performance index at Papah Irrigation Arrea in 2013 is 75,275 %. Thus, Papah Irrigation Area included in the good criteria and almost increased optimum value for the irrigation System Performance index in a irrigation area.